2021
DOI: 10.3390/jcm10112269
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Trimethylamine N-Oxide Is Associated with Increased Risk of Cardiovascular Mortality in Type-2 Diabetes: Results from a Dutch Diabetes Cohort (ZODIAC-59)

Abstract: Trimethylamine N-oxide (TMAO), a novel cardiovascular (CV) disease and mortality risk marker, is a gut microbiota-derived metabolite as well. Recently, plasma concentrations of branched-chain amino acids (BCAA) have been reported to be affected by microbiota. The association of plasma TMAO with CV mortality in Type 2 Diabetes (T2D) and its determinants are still incompletely described. We evaluated the association between plasma BCAA and TMAO, and the association of TMAO with CV mortality in T2D individuals. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Atherosclerosis hallmarks CHD, and efforts are currently being directed at better understanding the manner through which this inflammatory process contributes to the development of CHD. Trimethylamine N-oxide (TMAO), a gut microbial product derived from L-carnitine and choline-rich foods, has gained substantial attention due to its atherogenic potential and its impact on CHD prognosis and all-cause mortality [ 4 , 5 , 6 , 7 , 8 , 9 ]. Indeed, recent endeavors have suggested that higher admission plasma TMAO values reflect a larger atherosclerotic burden and a higher risk of plaque rupture in patients presenting with ST-segment elevation myocardial infarction (STEMI) prior to undergoing percutaneous coronary intervention (PCI) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis hallmarks CHD, and efforts are currently being directed at better understanding the manner through which this inflammatory process contributes to the development of CHD. Trimethylamine N-oxide (TMAO), a gut microbial product derived from L-carnitine and choline-rich foods, has gained substantial attention due to its atherogenic potential and its impact on CHD prognosis and all-cause mortality [ 4 , 5 , 6 , 7 , 8 , 9 ]. Indeed, recent endeavors have suggested that higher admission plasma TMAO values reflect a larger atherosclerotic burden and a higher risk of plaque rupture in patients presenting with ST-segment elevation myocardial infarction (STEMI) prior to undergoing percutaneous coronary intervention (PCI) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The updated meta-analysis on CVDs included 12 studies ( 4 , 6 , 83 , 91–96 ) with 22,945 participants and showed that high TMAO concentrations were statistically significantly associated with an increased risk of CVD (OR: 1.50; 95% CI: 1.26, 1.79; P = 8.00 × 10 −6 ) ( Figure 2 , Supplemental Figure 8 ). Eight studies from 5 articles ( 11 , 14 , 60 , 72 , 83 ) were used to perform a meta-analysis on CVD mortality. The results revealed that participants with high TMAO concentrations were more likely to die from CVDs than those with low TMAO concentrations (HR: 2.02; 95% CI: 1.74, 2.34; P = 6.01 × 10 −21 ) ( Figure 2 , Supplemental Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the updated meta-analyses showed no significant association between TMAO and DBP [14 studies ( 9 , 13–15 , 59 , 67 , 87–89 , 98 , 112–114 ) enrolling 10,085 subjects, WMD: −0.25; 95% CI: −0.95, 0.46; P = 0.495] ( Figure 4 , Supplemental Figure 15 ). Higher circulating TMAO was related to higher SBP [16 studies ( 3 , 9 , 13–15 , 59 , 67 , 87–89 , 98 , 112–115 ) enrolling 17,369 subjects, WMD: 1.92; 95% CI: 1.33, 2.51; P = 1.70 × 10 −10 ] ( Figure 4 , Supplemental Figure 16 ) and BMI [19 studies ( 3 , 9 , 13 , 14 , 53 , 65 , 67 , 84 , 87–90 , 98 , 103 , 113–116 ) enrolling 20,851 subjects, WMD: 0.54; 95% CI: 0.12, 0.97; P = 0.012] ( Figure 4 , Supplemental Figure 17 ). The association between TMAO concentrations and SBP remained significant when the meta-analysis included only cohort studies (WMD: 1.91; 95% CI: 1.39, 2.43; P = 6.85 × 10 −13 ) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations